P173 Investigating varicella-zoster virus-specific T cells through the lenses of HIV. (14th July 2019) - Moreira, Carolina; Perciani, Catia; Murooka, Thomas; Jaoko, Walter; Macdonald, Kelly; Team, KAVI-ICR
Abstract : Background: Varicella-zoster virus (VZV), also known as chickenpox virus, constitutes a promising vector for a successful HIV vaccine. As an effort to scrutinize its potential, we are characterizing the susceptibility of VZV-specific CD4 T cells to HIV infection and the phenotypic profile of both CD4 and CD8 T cells. Methods: Blood T cells isolated from a cohort of healthy Kenyan women with pre-immunity to VZV (NCT02514018 ) were stimulated in vitro using 15-mer peptides representing VZV glycoprotein E (gE) and VZV Open Reading Frame 4 (ORF4). CD4 and CD8 T cell memory phenotypes were characterized by flow cytometry based on the expression of CCR7/CD45RA. The activation status of VZV-specific CD4 T cells was measured by the expression of HLA-DR, CD69, and CD25 after 6-day stimulation with gE and ORF4 peptides. Susceptibility to HIV infection was assessed using in vitro infection with a CCR5-tropic virus. DMSO and CMV peptides were used as negative and positive controls, respectively. Results: A similar frequency of central memory CD4 T cells (TCM ) (median 24%, IQR 18%-32%) and effector memory CD4 T cells (TEM ) (median 27%, IQR 20%-32%) was observed in our cohort. The predominant CD8 memory subtype was TEMRA (median 28%, IQR 21%-40%) followed by TEM cells (median 12%, IQR 8%-19%) (n=45). Preliminary results show our ability to expand VZV-specific cells in culture using gE and ORF4 as stimuli and that these cells highly express the marker HLA-DR. Their susceptibility to in vitro HIV infection is currently under investigation using CMV-specific cells as comparator. Conclusion: A viral vector able to sustain CD8 TEM responses without fueling the immune system with HIV target cells constitutes an ideal candidate for an HIV vaccine. Hence, our study sheds light on key aspects of VZV-specific immunity that will help determining its future as a vector in an HIV vaccine. Disclosure: No significant relationships.